Galactosylated Prodrugs: A Strategy to Improve the Profile of Nonsteroidal Anti-Inflammatory Drugs - Federica Sodano; Claudia Cristiano; Barbara Rolando; Elisabetta Marini; Loretta Lazzarato; Mariarosaria Cuozzo; Stefania Albrizio; Roberto Russo; Maria Grazia Rimoli (MDPI AG, 2022)
Carbohydrates are one of the most abundant and important classes of biomolecules. The variety in their structures makes them valuable carriers that can improve the pharmaceutical phase, pharmacokinetics and pharmacodynamics of well-known drugs. D-galactose is a simple, naturally occurring monosaccharide sugar that has been extensively studied for use as a carrier and has proven to be valuable in this role. With the aim of validating the galactose-prodrug approach, we have investigated the galactosylated prodrugs ibuprofen, ketoprofen, flurbiprofen and indomethacin, which we have named IbuGAL, OkyGAL, FluGAL and IndoGAL, respectively. Their physicochemical profiles in terms of lipophilicity, solubility and chemical stability have been evaluated at different physiological pH values, as have human serum stability and serum protein binding. Ex vivo intestinal permeation experiments were performed to provide preliminary insights into the oral bioavailability of the galactosylated prodrugs. Finally, their anti-inflammatory, analgesic and ulcerogenic activities were investigated in vivo in mice after oral treatment. The present results, taken together with those of previous studies, undoubtedly validate the galactosylated prodrug strategy as a problem-solving technique that can overcome the disadvantages of NSAIDs.